(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
In the world of scientific publication, morals are not completely different than in daily life. There are cases of clear research misconduct. If misconduct occurs, it creates a disruption, not only for the scientific community and their institutions, but for all individuals involved. Journals aspire to select, through peer review, the highest quality science, and their reputations depend on the trust of readers, authors, researchers, and reviewers. This paper analyzes the major categories of ethical violations encountered during submission, review, and publication of scientific articles. The process of peer reviewing of the journals rely on expert and objective review by knowledgeable researchers to ensure the quality of the papers they publish. The review of manuscripts for peer reviewed journals raises many ethical issues and problems. The recommendations of the reviewers make concerning publication and the advice they give to authors set the scientific standards of the discipline. Understanding that some apparent ethical contraventions are the result of confusion or a lack of knowledge, some journals are assuming the responsibility of educating their community about ethical issues in publishing. The goal of this article is to make the guiding ethical principles accessible to all of our readers and contributors. By increasing education and awareness of ethical matters relevant to scientific investigation and publication, deviations from appropriate conduct will be reduced. In the future, authors can anticipate that their submissions will be required to meet an expanding array of ethical standards.